Analisis Pembelajaran Metode Tafahhum dalam Meningkatkan Pemahaman Al-Quran Siswa di Madrasah Aliyah Laboratorim UIN Sumatera Utara - Jannah, Raudhatul; Aida Nasution, Hasnil; Dahrul, Dahrul (Jurnal Ilmu Pendidikan Islam, 2024)
his study aims to analyze the Tafahhum Method learning in Improving Students' Understanding of the Qur'an at the UIN SU Laboratory Madrasah Aliyah and the factors that influence the Tafahhum Method in Improving Students' Understanding of the Qur'an at the UIN SU Laboratory Madrasah Aliyah. This study uses a qualitative approach with a descriptive method and field research type. The results of the study indicate that learning using the Tafahhum method in improving students' understanding of the Qur'an at the UIN SU Laboratory Madrasah Aliyah is using a Conceptual approach, Deepening of Meaning, improving critical thinking skills, practical application, Spiritual and Moral Development, and Social Interaction and discussion. The factors that influence the tafahhum method in improving students' understanding of the Qur'an at the UIN SU Laboratory Madrasah Aliyah include: The main factor is because there are so many students who, with their family background or perhaps their environmental circumstances, are indeed lacking in understanding the Qur'an, so it's as if at the high school level the teacher will reintroduce them like elementary school students, the teacher explains things that they should probably know, but the biggest factor is that they don't understand it clearly and the second factor is related to the very little time which makes the delivery very limited.